(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Women can be considered as one of the most important human resources of the society. The status of women in a society is an indicator of the quality of social organizations of that society. Therefore, the development of the entire world is not possible without the upgradation of women’s condition and empowerment, and the best tool for this women empowerment is education. During the British period, education became a tool of colonial domination, although only a minority had access to that education and were able to enjoy all its benefits. It was in this context that the social reformers of the 19th century raised the demand for women’s education. However, despite various efforts, women are somehow deprived of education and other basic rights due to various reasons such as poverty, child marriage, gender discrimination, inequality etc. West Bengal as a state of India is no exception. Therefore, with the aim of overall development and empowerment of girls in West Bengal, in 2013, under the inspiration of Hon’ble Chief Minister Ms. Mamata Banerjee, the Women and Child Development and Social Welfare Department of West Bengal Government launched the Kanyashree Project, which aims to prevent school dropout, child marriage and child pregnancy aiming to empower adolescent girls through financial independence. This research paper aims to confirm whether Kanyashree project plays an active role in improving the social status of women and thereby empower them? - Attempts have been made to uncover it. In this case, the role of Kanyashree project in promoting women’s education and ensuring self-reliance has been explored in a primary study of 100 kanyashrees in selected women colleges in North 24 Parganas and the awareness of the beneficiaries about their position has been verified.